Performance Assessment of Dual-Powered Baking Oven Developed from Locally Sourced Materials - Awode, E. I.; Abutu, J.; Garkuwa, H. (Journal of Advanced Industrial Technology and Application, 2023)
In this study, a dual-powered baking oven (electric and gas) was developed using locally available materials with the aim of investigating the performance of the constructed oven using standard test procedure. The performance of the constructed baking system was assessed by investigating the quantity of heat supplied, gas expended, moisture content and drying rate. The experimental results revealed that more heat is supplied during the baking of bread using electrical part of the system while high moisture content and drying rate was recorded during the roasting of fish using electricity. However, the highest (39.742kJ) and lowest (0.334kJ) heat supplied was obtained in the 15th and 6th minutes respectively during the baking of bread with electricity and gas respectively. Hence, it can be concluded that the use of electricity in baking or roasting is capable of enhancing an efficient and effective baking processes